1981
DOI: 10.1271/bbb1961.45.2675
|View full text |Cite
|
Sign up to set email alerts
|

Raw starch-digestive glucoamylase productivity of protease-less mutant from Aspergillus awamori var. kawachi.

Abstract: Mutation experiments were performed to decrease the protease productivity of Aspergillus awamori var. kawachi using ultraviolet light and TV-methyl-TV'-nitro-TV-nitrosoguanidine. The selected mutant HF-15 showed reductions in protease productivity of 93%, 84% and 50% in solid wheat bran culture, shaking MediumB and wheat bran cultures, respectively, as compared with the parent. Protease-less mutant HF-15 failed to produce a-mannosidase, and iV-acetyl-/?-Dglucosaminidase productivity decreased by 35%. Mutant HF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Many other reports have also mentioned that glucoamylase of Aspergillus sp. exists in two to four isoforms, which vary from species to species [15].…”
Section: Resultsmentioning
confidence: 99%
“…Many other reports have also mentioned that glucoamylase of Aspergillus sp. exists in two to four isoforms, which vary from species to species [15].…”
Section: Resultsmentioning
confidence: 99%
“…kawachi by protease or glycosidase. A protease-negative mutant of this organism produced but one form of amyloglucosidase (Hayashida and Flor, 1981). Four forms of the enzyme showed different susceptibilities to two proteases (Paszczynski et ai., 1985) in the culture medium of A. niger C. It has been suggested that these two proteases may regulate amyloglucosidase activity and heterogeneity.…”
Section: Amyloglucosidasementioning
confidence: 99%
“…We further showed that the protease-negative, glycosidase-negative mutant strain HF-15 of A. awamori var. kawachi produced only raw-starch-digesting glucoamylase GA 0 (MW 250,000; type A) under any conditions of submerged or solid culture (3,5,6). On the basis of these results with glucoamylase, we expected the presence of raw-starch-digesting a-amylase from fungi and tried to isolate the protease-negative mutant that could produce a high amount of a raw-starchadsorbable, raw-starch-digesting a-amylase.…”
mentioning
confidence: 99%